Antibiotic Resistances and Molecular Characteristics of Clostridioides difficile in ICUs in a Teaching Hospital From Central South China - Meng, Xiujuan; Huang, Xun; Peng, Zhong; Wang, Yaowang; Liu, Sidi; Zeng, Cui; Duan, Juping; Wen, Ximao; Fu, Chenchao; Wu, Anhua; Li, Chunhui (Frontiers in Medicine, 2021)
Clostridioides (C.) difficile is a major healthcare-associated pathogen inducing infectious diarrhea. Approximately 25–33% of patients with antibiotic-associated diarrhea (AAD) and 90% of patients with pseudomembranous enteritis are caused by C. difficile infection (CDI). Stool samples were collected from hospitalized adults with presumptive AAD in four nonneonatal intensive care units (ICUs). Diagnosis of CDI was based on both clinical symptoms and laboratory results. The stool specimens were transferred onto CDIF (C. difficile agar), and C. difficile was finally confirmed by the latex agglutination test. Toxin-producing genes tcdA (A), tcdB (B), and cdt (CDT) were detected by PCR, and all isolates were performed multilocus sequence typing analysis. The antibiotic susceptibility of C. difficile isolates was assessed by the agar dilution method. A total of 184 C. difficile were isolated from 857 specimens in our study, the isolation rate of C. difficile was 21.5% (184/857). The 184 C. difficile were isolated from 179 patients, among these 115 patients were toxin-positive, giving the incidence of CDI being 58.0/10,000 patient days in the four ICUs. Among these 115 toxin-positive C. difficile isolates, 100 (87.0%) isolates produced two toxins (A+B+CDT-), three (2.6%) isolates were A+B+ with binary toxin-producing (A+B+CDT+), and 12 (10.4%) isolates only produced one toxin (A-B+CDT-). A total of 27 sequencing types (STs) were obtained. The most prevalent was ST3 (34 isolates), followed by ST39 (27 isolates), ST54 (19 isolates), ST26 (16 isolates), ST35 (15 isolates), and ST2 (13 isolates). All the ST26 isolates were nontoxigenic. Meanwhile, five STs were newly discovered. Although multidrug resistance was present in ≥50% of these C. difficile isolates, all of them were susceptible to tigecycline, fidaxomicin, metronidazole, and vancomycin. In conclusion, C. difficile isolates producing two toxins (A+B+CDT-) were dominant in our hospital. The most prevalent was ST3, and all ST26 isolates were NTCD. Although multidrug resistance was present in ≥50% of the C. difficile isolates, metronidazole, tigecycline, fidaxomicin, and vancomycin were still effective treatments for CDI in our hospital.